Treating the abusive partner : an individualized cognitive-behavioral approach - Murphy, Christopher M. (Christopher Mark) (Guilford Press, 2005)
Intimate partner violence is notoriously difficult to treat, and this promising manual presents the first one-on-one cognitive-behavioral treatment approach for this highly challenging population. Provided are a straightforward rationale and clear guidelines for implementing the authors' flexible four-phase model, which is grounded in extensive research and clinical experience. Detailed case examples illustrate the complexities of conceptualizing individual cases and working with clients to enhance motivation for change, eliminate assaultive and threatening behaviors, alter abuse-maintaining s.